Hominoid anterior teeth from the late Oligocene site of Losodok, Kenya. Issue 128 (March 2019) - Hammond, Ashley S.; Foecke, Kimberly K.; Kelley, Jay
Abstract: Kamoyapithecus hamiltoni is a potential early hominoid species described from fragmentary dentognathic specimens from the Oligocene site of Losodok (Turkana Basin, northwestern Kenya). Other catarrhine dental materials have been recovered at Losodok, but were not initially included in the Kamoyapithecus hypodigm. Here we present descriptions of the unpublished canine and incisor specimens from Losodok, and revisit the published specimens in light of recent changes in understanding of hominoid anterior dental evolution. The new fossils include a canine (KNM-LS 18354) that is morphologically compatible with being a female of Kamoyapithecus (KNM-LS 8). Randomization analyses of both Gorilla gorilla and middle Miocene Griphopithecus alpani demonstrate that the size difference between KNM-LS 8 and KNM-LS 18354 is also compatible with their being male and female canines of the same species. Significantly, a canine tip (KNM-LS 18352) attributed to Kamoyapithecus documents the distinctive burin tip morphology now recognized as characterizing Proconsul sensu stricto, which may indicate a close relationship between Kamoyapithecus and Proconsul . We also re-examined the enigmatic KNM-LS 1, a smaller lower canine assumed to derive from Losodok but for which historical provenience data are completely lacking. Elemental data derived from portable X-ray fluorescence spectroscopy show that KNM-LS 1 is almost certainly from Losodok rather than from nearby Miocene sites (i.e., Moruorot, Esha, Kalodirr). KNM-LS 1 displays a nyanzapithecine-like morphology and is shown by randomization analyses to be too small to be associated with the Kamoyapithecus canines. This demonstrates that there is a second hominoid taxon present at Losodok that records one of the earliest occurrences of the Nyanzapithecinae.